Zone of Transition: A Potential Source of Error in Tumor Volume Estimation(1) - Zhang, Lijuan (Radiological Society of North America, Inc., 2010)
PURPOSE: To measure the width of the zone of transition (ZOT) between nonaerated solid tumor and surrounding nonneoplastic lung parenchyma and determine the extent to which ZOT influences computer-derived estimates of tumor volume based on computed tomographic (CT) images. MATERIALS AND METHODS: This HIPAA-compliant study was approved by the institutional research board. The histologic slide containing the maximum tumor area was digitized for 20 consecutive patients with solid adenocarcinoma. The outer border of the tumor (A2) was marked; it included all lung parenchyma having any tumor cells. The inner border of the tumor (A1) was marked; it included only solid tumor where lung parenchyma was no longer preserved. Assuming two circles with areas of A2 and A1, the corresponding two radii, R2 and R1, were calculated. The average width of the ZOT was defined as R2 minus R1. The relationship between ZOT and tumor diameter on the CT images prior to surgery was assessed by using regression analysis. The relationship between ZOT and tumor volume was assessed by using a theoretical model of idealized spheres with varying diameters. RESULTS: The mean width of the ZOT was 0.78 mm (median, 0.48 mm). The proportional effect of ZOT on tumor volume estimates decreased with increasing tumor diameter and increased with increasing width of ZOT. Correlation between ZOT and tumor diameter was not significant (P = .87). CONCLUSION: The average width of ZOT is about a single pixel width on a full field of view CT scan; thus, the ZOT can have a large effect on volume estimates, particularly for small tumors. © RSNA, 2010